2016
DOI: 10.3389/fnsys.2015.00178
|View full text |Cite
|
Sign up to set email alerts
|

Models of Innate Neural Attractors and Their Applications for Neural Information Processing

Abstract: In this work we reveal and explore a new class of attractor neural networks, based on inborn connections provided by model molecular markers, the molecular marker based attractor neural networks (MMBANN). Each set of markers has a metric, which is used to make connections between neurons containing the markers. We have explored conditions for the existence of attractor states, critical relations between their parameters and the spectrum of single neuron models, which can implement the MMBANN. Besides, we descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Usually, w = 1 and r = 0. In computational experiments [2] we have explored the methods for making inter-neuronal connections, which enable the neural networks to have attractor states (states which are transformed into themselves under the specified above rules of neural dynamics). The states of the neural network are N-dimensional vectors of ones (neuron is excited) and zeros (neuron is quiet).…”
Section: Inborn Attractorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Usually, w = 1 and r = 0. In computational experiments [2] we have explored the methods for making inter-neuronal connections, which enable the neural networks to have attractor states (states which are transformed into themselves under the specified above rules of neural dynamics). The states of the neural network are N-dimensional vectors of ones (neuron is excited) and zeros (neuron is quiet).…”
Section: Inborn Attractorsmentioning
confidence: 99%
“…As soon as the markers are distributed between the neurons, the latter are connected with excitatory synapses. The connections are symmetric and are set between two neurons, if they have markers, the distance between which is less, than another pre-determined value, į. Computational experiments have demonstrated that the two types of metrics marks, described above, yield the neural networks with the SAAS with d = 0 and the SAAS with d = 1, when the same for both cases conditions for marker distribution and connection setting have been used [2].…”
Section: Inborn Attractorsmentioning
confidence: 99%
See 3 more Smart Citations